ZINC SERUM LEVEL AND PERIPHERAL BLOOD MONOCYTE COUNT OF MULTIBACILAR LEPROSY PATIENT LOWER THAN PAUCIBACILAR LEPROSY IN RSUP SANGLAH - Kurniawan Dhana, Putu; Darma Putra, IGN; Wardhana, Made (Medicina; Vol 43 No 3 (2012): September 2012, 2013)
Zinc has been known to have important role in the immune system. Zinc deficiency can inhibit activation and production cytokine of Th1 and  may cause cellular immunity dysfunction. This conditon also may cause changes of lymphopoiesis and hematopoiesis also peripheral blood of mononuclear cell as mononuclear fagocyte. The Aim of this study is to know zinc serum status and peripheral blood monocyte count of leprosy patient in Dermato Venerologi policlinic Sanglah hospital Denpasar. This study use cross sectional design. Sample of study take by consecutive sampling with sample size contains 75 patient.  Mean of zinc serum status on multibacillary leprosy patient is 5.66  (SB 11.74 ) found lower compare to paucibacillary leprosy patient 19.38 (SB 18.21) and statistically significant with P < 0.05. Mean of peripheral blood monocyte count in multibacillary patient is 7.12 (SB 2.53) lower compare to paucibacillary leprosy patient with 7.88 (SB 3.08), but statistically not significant with P > 0.05. Binary logistic analysis show the influence of zinc serum status to probability to have leprosy. This study suggest correction of serum zinc level in leprosy patient through nutritional approach or the granting of a supplement of zinc
Keywords: mean zinc serum, monocyte, leprosy